Fidelity - Paley, Grace 1922-2007 (Farrar, Straus and Giroux, 2008)
Just before her death in 2007 at the age of eighty-four, Grace Paley completed this wise and poignant book of poems. Full of memories of friends and family and incisive observations of life in both her beloved hometown, New York City, and rural Vermont, the poems are sober and playful, experimenting with form while remaining eminently readable. They explore the beginnings and ends of relationships, the ties that bind siblings, the workings of dreams, the surreal strangeness of the aging body--all imbued with her unique perspective and voice. Mournful and nostalgic, but also ruefully funny and full of love, Fidelity is Grace Paley's passionate and haunting elegy for the life she was leaving behind. -- Publisher's description.
Keywords: Poetry